2017
DOI: 10.1016/s2213-2600(17)30310-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel formulation of inhaled sodium cromoglicate (PA101) in idiopathic pulmonary fibrosis and chronic cough: a randomised, double-blind, proof-of-concept, phase 2 trial

Abstract: Patara Pharma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 58 publications
3
77
0
2
Order By: Relevance
“…The study was not designed to detect subgroup effects, so significant improvement in LCQ for the CC with asthma subgroup maybe a chance finding rather than a true treatment effect. No objective cough measurement used.Birring et al, 2017 [125]Multicenter, double-blind, randomized placebo-controlled, 2-period cross-over trial (Phase IIa study) in patients with IPF and chronic cough and a parallel study of similar design in patients with refractory CC.27 PA101 cromolyn sodium formulation (40 mg) or matching placebo three times a day via oral inhalation for 2 weeks, followed by a 2 week washout, and then crossed over to the other arm.Primary efficacy outcome was change from baseline in objective daytime cough frequency (from 24 h acoustic recording, Leicester Cough Monitor) to posttreatment. Secondary cough outcomes included the LCQ, and cough severity (VAS).In patients with IPF, PA101 significantly reduced daytime cough frequency by 31.1% at day 14 compared with placebo (ratio of least-squares [LS] means 0.67, 95% CI 0.48–0.94, p  = 0.0241).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was not designed to detect subgroup effects, so significant improvement in LCQ for the CC with asthma subgroup maybe a chance finding rather than a true treatment effect. No objective cough measurement used.Birring et al, 2017 [125]Multicenter, double-blind, randomized placebo-controlled, 2-period cross-over trial (Phase IIa study) in patients with IPF and chronic cough and a parallel study of similar design in patients with refractory CC.27 PA101 cromolyn sodium formulation (40 mg) or matching placebo three times a day via oral inhalation for 2 weeks, followed by a 2 week washout, and then crossed over to the other arm.Primary efficacy outcome was change from baseline in objective daytime cough frequency (from 24 h acoustic recording, Leicester Cough Monitor) to posttreatment. Secondary cough outcomes included the LCQ, and cough severity (VAS).In patients with IPF, PA101 significantly reduced daytime cough frequency by 31.1% at day 14 compared with placebo (ratio of least-squares [LS] means 0.67, 95% CI 0.48–0.94, p  = 0.0241).…”
Section: Resultsmentioning
confidence: 99%
“…Inhaled sodium cromoglicate has been shown to inhibit both allergen-induced early and late asthmatic responses and exercise-induced asthma [123,124]. Birring et al [125] very recently assessed the efficacy and safety of inhaled PA101 in a randomized placebo-controlled trial in patients with idiopathic pulmonary fibrosis (IPF) and CC and a parallel study of similar design in patients with refractory CC. The primary efficacy endpoint was change from baseline to posttreatment daytime cough frequency using the LCM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent pilot study of a novel formulation of inhaled cromolyn sodium (PA101) showed promise. 20 There was a >30% reduction in objective cough frequency between the treatment and placebo periods that is likely to be clinically significant. Although there was no significant change in the subjective cough severity and quality of life measures with treatment, the study was not powered to detect these, and the treatment duration was short.…”
Section: Corticosteroids In Ipf (In Combination Withmentioning
confidence: 97%
“…Finally, three systematic reviews that met our inclusion criteria were excluded because the only relevant studies they contained were already included in our review. [17][18][19] Three papers [20][21][22] met the inclusion criteria but were published after the initial search and were subsequently included on agreement of all the authors of the expert panel report. This process resulted in 10 studies included in this review ( Table 2).…”
Section: Grading Recommendationsmentioning
confidence: 99%